The Curriculum Basis of Islamic Education Perspective Ali Ahmad Madzkur - Yanti Nurdiyanti; Mohammad Yamin; Izzudin Mustafa (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
This article aims to examine the underlying basis for the preparation of an Islamic education curriculum from the perspective of Ali Ahmad Madzkur. The type of research used is library research or library research where the problems and data collection of this research are sourced from primary data (principal) and secondary data (supporting data), the data collection technique in this study is documentation, and the method used in analyzing the data is analyzed the content in a data or content analysis (content analysis). The results of this study found that Islamic education has three main foundations, namely: educational philosophy, learner character, and social character. The Islamic education curriculum is structured based on four foundations; First, the Islamic concept of the divine reality, the second is the conception of the universe, the third is the conception of the nature of human instincts, and the fourth is the concept of life with various things in it such as politics, economics, social, cultural and cognitive organization, as well as the concept of the relationship between them. The basics of education curriculum construction in the Islamic conception are based on these four foundations.